El tratamiento de la naturaleza en los autos sacramentales de Lope: modos constructivos de un topos alegórico - Juan Manuel Escudero Baztán (Criticón)
Lope’s treatment of nature in his sacramental plays is a good example of the use of allegorical techniques to convert a real space into a fictitious one, where predominate the idealized landscape of the pastoral world and the popular side of the agricultural space. This identification of the planes of «the human and divine letters» is carried out through the attributes of shepherd and lamb that Christ receives in biblical and patristic exegesis. And it is concretized with the use of a series of extensive paradigms (which affect the sacramental play as a whole) and other shorter ones, which point to very varied and widespread specific themes and motifs in other secular genres of the Golden theater.